2019
DOI: 10.1016/j.evolhumbehav.2018.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Chimpanzees and children avoid mutual defection in a social dilemma

Abstract: Cooperation often comes with the temptation to defect and benefit at the cost of others. This tension between cooperation and defection is best captured in social dilemmas like the Prisoner's Dilemma. Adult humans have specific strategies to maintain cooperation during Prisoner's Dilemma interactions. Yet, little is known about the ontogenetic and phylogenetic origins of human decision-making strategies in conflict scenarios. To shed light on this question, we compared the strategies used by chimpanzees and 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 67 publications
4
12
1
1
Order By: Relevance
“…The results of the study suggest that pairs of gibbons can solve a con ict of interest where one pair member has the opportunity to volunteer to activate a release mechanism containing potential food rewards for both partners. In line with previous studies with great apes, gibbons avoided mutual defection in a Test condition where they could obtain a direct reward from their actions 10,47 . In contrast, in an Altruistic condition where gibbons could not obtain direct bene ts, their likelihood to volunteer and release potential food rewards dropped signi cantly in comparison to the Test condition.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of the study suggest that pairs of gibbons can solve a con ict of interest where one pair member has the opportunity to volunteer to activate a release mechanism containing potential food rewards for both partners. In line with previous studies with great apes, gibbons avoided mutual defection in a Test condition where they could obtain a direct reward from their actions 10,47 . In contrast, in an Altruistic condition where gibbons could not obtain direct bene ts, their likelihood to volunteer and release potential food rewards dropped signi cantly in comparison to the Test condition.…”
Section: Discussionsupporting
confidence: 86%
“…Using a different approach, other researchers have presented great apes, mostly chimpanzees (Pan troglodytes), with non-computerized social dilemmas in which apes had to decide between different physical actions to obtain rewards from an apparatus. In general, these studies have found that chimpanzees and bonobos develop strategies to outcompete their partners and obtain the most from the social dilemma, either through monopolization of rewards 9 , by waiting for their partner to act before them 8,10,15 or by in uencing them to change their strategy 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The increased levels of cooperation seen in the capuchin monkeys in this study is somewhat inconsistent with previous research on the PD in primates. A similar computerized task with rhesus macaques showed that the monkeys demonstrated low levels of mutual cooperation (Haroush & Williams, ), while in a more naturalistic manual task with chimpanzees, where subjects could defect upon their partner's cooperation by not pulling a rope and then monopolizing the food reward the partner brought in, researchers found that while the chimpanzees frequently coordinated behavior, they would often wait until their partner pulled to at least minimize their personal effort when they did eventually pull (Sánchez‐Amaro, Duguid, Call, & Tomasello, ).…”
Section: Discussionmentioning
confidence: 99%
“…where subjects could defect upon their partner's cooperation by not pulling a rope and then monopolizing the food reward the partner brought in, researchers found that while the chimpanzees frequently coordinated behavior, they would often wait until their partner pulled to at least minimize their personal effort when they did eventually pull (Sánchez-Amaro, Duguid, Call, & Tomasello, 2019).…”
Section: F I G U R Ementioning
confidence: 99%
“…To that end, in the current study we compared behavior in six prosocial behavior games: three variants of a social dilemma game and three more naturalistic games, where people were asked to build puzzles together (Vink, Hasselman, Cillessen, Wijnants, & Bosman, 2018), communicate and exchange information (Nevicka, Ten Velden, de Hoogh, & van Vianen, 2011), and help each other in collecting eggs (McClung, Placì, Bangerter, Clément, & Bshary, 2017). With regard to the social dilemma games, we tested three variants of the Prisoner's Dilemma game: (1) the classical variant with two response options (cooperate or defect); (2) an extended version of the Prisoner's Dilemma game, where the pay-off structure was extended from a 2 x 2 to a 6 x 6 matrix; and (3) an adjusted version developed to test children and chimpanzees, where participants can decide to pull a rope (i.e., cooperate) or not (i.e., defect) (Sánchez-Amaro, Duguid, Call, & Tomasello, 2019). Including these three variants allowed us to investigate whether participants based their decision on the same principles across games despite changes in the scale (six versus two response options) and the way of indicating a decision (key press versus rope pull).…”
mentioning
confidence: 99%